Second- and third-generation drugs for immuno-oncology treatment—The more the better?. (March 2017) - Dempke, Wolfram C.M.; Fenchel, Klaus; Uciechowski, Peter; Dale, Stephen P.
Abstract: Recent success in cancer immunotherapy (anti-CTLA-4, anti-PD1/PD-L1) has confirmed the hypothesis that the immune system can control many cancers across various histologies, in some cases producing durable responses in a way not seen with many small-molecule drugs. However, only less than 25% of all patients do respond to immuno-oncology drugs and several resistance mechanisms have been identified (e.g. T-cell exhaustion, overexpression of caspase-8 and β-catenin, PD-1/PD-L1 gene amplification, MHC-I/II mutations). To improve response rates and to overcome resistance, novel second- and third-generation immuno-oncology drugs are currently evaluated in ongoing phase I/II trials (either alone or in combination) including novel inhibitory compounds (e.g. TIM-3, VISTA, LAG-3, IDO, KIR) and newly developed co-stimulatory antibodies (e.g. CD40, GITR, OX40, CD137, ICOS). It is important to note that co-stimulatory agents strikingly differ in their proposed mechanism of action compared with monoclonal antibodies that accomplish immune activation by blocking negative checkpoint molecules such as CTLA-4 or PD-1/PD-1 or others. Indeed, the prospect of combining agonistic with antagonistic agents is enticing and represents a real immunologic opportunity to 'step on the gas' while 'cutting the brakes', although this strategy as a novel cancer therapy has not been universally endorsed so far. Concerns include the prospect of triggering cytokine-release syndromes, autoimmune reactions and hyper immune stimulation leading to activation-induced cell death or tolerance, however, toxicity has not been a major issue in the clinical trials reported so far. Although initial phase I/II clinical trials of agonistic and novel antagonistic drugs have shown highly promising results in the absence of disabling toxicity, both in single-agent studies and in combination with chemotherapy or other immune system targeting drugs; however, numerous questions remain about dose, schedule, route of administration and formulation as well as identifying the appropriate patient populations. In our view, with such a wealth of potential mechanisms of action and with the ability to fine-tune monoclonal antibody structure and function to suit particular requirements, the second and third wave of immuno-oncology drugs are likely to provide rapid advances with new combinations of novel immunotherapy (especially co-stimulatory antibodies). Here, we will review the mechanisms of action and the clinical data of these new antibodies and discuss the major issues facing this rapidly evolving field.